A Comparative Study of Serum Pharmacochemistry of Kai-Xin-San in Normal and AD Rats Using UPLC-LTQ-Orbitrap-MS - Lin Yang; Jian Liang; Qin Zheng; Lifen Zhou; Yongchang Xiong; Huijuan Wang; Jinbin Yuan (MDPI AG, 2022)
Kai-Xin-San (KXS) is a classic formula for the treatment of Alzheimer's disease (AD). KXS has been widely used to treat emotional diseases; however, its active components remain unknown. There have been some reports about the efficacy and metabolic analysis of KXS, which are mainly based on studying normal animals. The current work first established an AD rat model by injecting D-galactose into the abdominal cavity and injecting Aβ25-35 into the hippocampus on both sides, followed by intragastric administration of KXS for a consecutive week; then, the analytical method for ethanol extraction from the serum of normal and model rats was developed using UPLC-LTQ-Orbitrap-MS; finally, the transitional components in the blood were systematically compared and analyzed by multivariate statistical analysis. A total of 36 components of KXS were identified in the rat serum of the normal group, including 24 prototype components (including ginsenosides, triterpenoid acids of Poria cocos, polygala saponins, polygala xanthones and polygala ester) and 13 metabolites (including desugar, hydration and oxidation products of ginsenosides, triterpenoid acid hydroxylation, deoxygenation, demethylation, desaturation, and glycine-conjugated products of Poria cocos). Twenty KXS-relevant components were detected in the rat serum of the model group, including 11 prototypes and 9 metabolites. The normal group and the model group shared 12 common components, including 9 prototypes and 3 metabolites. The intestinal microecological balance of the model rats probably was destroyed, affecting the absorption/metabolism of saponins by the body, which resulted in fewer transitional components in the model group. This study reflected the drug-body interaction from an objective and accurate perspective, offering references and insights for elucidating the basis of active components and mechanism of action of KXS for treating AD.